Lie Group Solutions of Magnetohydrodynamics Equations and Their Well-Posedness - Fu-zhi Li; Jia-li Yu; Yang-rong Li; Gan-shan Yang (Abstract and Applied Analysis)
Based on classical Lie Group method, we construct a class of explicit solutions of two-dimensional ideal incompressible magnetohydrodynamics (MHD) equation by its infinitesimal generator. Via these explicit solutions we study the uniqueness and stability of initial-boundary problem on MHD.